Flatid Planthopper, Oormenaria rufifascia (Walker) (Insecta: Hemiptera: Auchenorrhyncha: Flatidae) - Forrest W. Howard; Susan Halbert (EDIS)
Ormenaria rufifascia (Walker) is a common insect on some species of palms in Florida. Although it is usually not a serious pest, it sometimes indirectly causes aesthetic damage when dense populations produce honeydew that supports extensive coatings of sootymold on the host plants. Both the adults and nymphs are conspicuous insects that often arouse people's curiosity.  This document is EENY-351 (IN643), one of a series of Featured Creatures from the Entomology and Nematology Department, UF/IFAS Extension. Published July 2005.